Sowing time and density on the agronomic performance of irrigated rice in the pre germinated system - Martins Júnior, Marcos Cardoso (2021)
In recent years, paddy rice growers from the south of Santa Catarina, Brazil, have anticipated the sowing date to the beginning of September, aiming to harvest the crop ratoon. In addition to that, they have increased the sowing density to mitigate the smaller plant growth. The objective of this work was to analyze the effects of sowing time and density on the agronomic performance of pregerminated rice. The experiment was set in the city of Praia Grande, SC, Brazil, during the 2018/2019 growing season.  A randomized block design was used, with treatments arranged in split plots. Three sowing dates were tested in the main plots: September 10 (early sowing), October 15 (preferential sowing), and November 20 (late sowing). Four sowing densities were evaluated in the split plots: 80 kg, 120 kg, 160 kg, and 200 kg of seeds per hectare. Morphological characteristics and the yield and components of grains were assessed. Grain yield ranged from 6,277 kg ha-1 to 9,605 kg ha-1 and was affected by the interaction between sowing date and density. The highest yield was achieved when rice was sowed on October 15 at the density of 120 kg ha-1. On the earliest sowing date, grain yield increased linearly by 12.54 kg ha-1 for each kg of added seed above the lowest density evaluated in the trial. The highest grain productivity achieved on this sowing date was 7,858 kg ha-1. Plant density had a small impact on rice yield at the latest sowing date. The highest yield at this planting time (8,546 kg ha-1) was gathered at the density of 120 kg ha-1.  The optimum seed density to maximize pregerminated rice yield in the south of Santa Catarina depends on the sowing date and is higher when the crop is sowed early.